Serum Concentrations of Osteogenesis/Osteolysis-Related Factors and Micro-RNA Expression in ST-Elevation Myocardial Infarction - Tomasz Jadczyk; Tomasz Francuz; Wojciech Garczorz; Malgorzata Kimsa-Furdzik; Mieczyslaw Dutka; Ewa Gaik; Katarzyna Gruszczynska; Marcin Syzdol; Wojciech Wanha; Radoslaw Kurzelowski; Joanna Fluder; Zdenek Starek; et al. (Cardiology Research and Practice)
Background. Atherosclerosis and bone metabolism share similar molecular and cellular mechanisms. This study aims to evaluate (1) serum concentration of osteogenesis/osteolysis factors panel (Dickkopf-related protein 1 (DKK-1), TNF-α, N-terminal atrial natriuretic peptide (NT-proANP), thrombospondin-2 (TSP-2), osteoprotegerin (OPG), osteocalcin (OCN), osteopontin (OPN), fibroblast growth factor 23 (FGF-23), soluble receptor activator of nuclear factor-kappaB ligand (sRANKL), tumor necrosis factor-related apoptosis-inducing ligand (TRAIL), proprotein convertase subtilisin/kexin type 9 (PCSK9)), (2) serum expression levels of micro-RNA- (miR-) 24-1 and miR-6802, and (3) assess their correlation with myocardial injury and LV remodeling and function in the acute phase of STEMI and after 3 months. Methods. Study enrolled 25 STEMI patients (mean age 55.4 ± 8.96 years). Blood samples were collected 4 days and 3 months after myocardial infarction. Serum concentrations of osteogenesis/osteolysis factors were measured using the Luminex assay. Analysis of miR-24-1, and miR-6802 expression was performed with qPCR. LV function and remodeling were assessed by MRI during index hospitalization and 3 months later. Results. There were no significant differences in serum levels of osteogenesis/osteolysis factors and expression of miR-24-1 and miR-6802 between the acute phase and 3-month follow-up. The levels were similar in patients with at least ≥5% improvement of LVEF (n = 10) and those without improvement. There was a negative correlation between the OPG serum level and LVEF during the acute phase of myocardial infarction. Conclusions. In STEMI patients, serum concentrations of osteogenesis/osteolysis factors, as well as miR-24-1 and miR-6802 expression, do not change significantly within the 3-month follow-up and are not correlated with LV remodeling and function.